2014
DOI: 10.1177/0883073814534318
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Quality of Life in High School Students

Abstract: The aim of the study was to estimate quality of life and determine the adjusted association of migraine with the quality of life in a sample of students. This population-based study was performed among 857 high school students in Boukan City (with a Kurdish language-speaking population, about 600 km west of the city of Tehran, Iran). The World Health Organization Quality of Life questionnaire was used along with International Headache Society criteria. Multiple linear regression models were applied. The mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…62 An adult study also reported an independent association of selfreported depression and worse QoL in children with headache. 63 Contrary to the results from a past study, 28 we did not find a link between sociodemographic factors and QoLs of children with headache. Until date, research studies have not usually focused the headache-specific, psychiatric, and sociodemographic factors together, and mixed results regarding the determinants of QoL seem to be stem from methodological differences among studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…62 An adult study also reported an independent association of selfreported depression and worse QoL in children with headache. 63 Contrary to the results from a past study, 28 we did not find a link between sociodemographic factors and QoLs of children with headache. Until date, research studies have not usually focused the headache-specific, psychiatric, and sociodemographic factors together, and mixed results regarding the determinants of QoL seem to be stem from methodological differences among studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of previous studies have consistently shown chronic headaches to have an adverse impact on the QOL of affected children. [25][26][27][28][29] Some studies also compared the QoL of children with migraine with that of children with TTH and found no significant difference between the two groups. 25,30 There is an uncertainty regarding the determinants of QoL in children with headache due to methodological differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That this is not the case for other populations is underlined by contradictory results in literature. Some migraineurs felt a subjective lack of support by their siblings [47] and had significantly reduced scores in social relationship compared to healthy children, having a lower ability to communicate in school and social environment [48]. Whether there is an association between social relationships and migraine is hard to assess, due to conflicting outcomes from literature.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] These data are also important given that there is concern about migraine and stigma, and because patients report decreased quality of life compared to their peers. [22][23][24] Increased education and awareness among students and spread of this knowledge to their families could lead to increased diagnosis and treatment for migraine and concussion, thereby decreasing the time of onset to diagnosis for these conditions. Finally, despite our small sample size, there appeared to be improvement in knowledge based on differences in the preassessment and subsequent assessments.…”
Section: Discussionmentioning
confidence: 99%